2017
DOI: 10.17707/agricultforest.63.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Common Bean (Phaseolus Vulgaris L.) Genotypes for Disease Tolerance Under Rain-Fed Conditions

Abstract: SUMMARYBreeding for disease tolerance in common bean (Phaseolus vulgaris L.) can improve yields for small-scale and commercial bean producers. This study evaluated promising common bean (Phaseolus vulgaris L.) genotypes for disease tolerance under rain-fed conditions at Harare Research Centre in Zimbabwe. A total of 25 genotypes, sourced from the International Center for Tropical Agriculture (CIAT), Malawi and Crop Breeding Institute (CBI), Harare were used in the experiment. These were replicated three times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Previously, similar research results were also reported in Turkey and in different parts of the world for differentiating the interaction between different bean genotypes with CBB pathogen and identifying some potential genotypes which had a resistant gene for CBB resistance breeding activities (Dursun et al, (2002;Donmez et al, 2013;Ararsa et al, 2017;Alladassi et al, 2018). On the contrary, Benlioğlu et al (1994) and Takudzwa et al (2017) showed that none of the evaluated beans were immune and resistant to CBB in Turkey and Serbia, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Previously, similar research results were also reported in Turkey and in different parts of the world for differentiating the interaction between different bean genotypes with CBB pathogen and identifying some potential genotypes which had a resistant gene for CBB resistance breeding activities (Dursun et al, (2002;Donmez et al, 2013;Ararsa et al, 2017;Alladassi et al, 2018). On the contrary, Benlioğlu et al (1994) and Takudzwa et al (2017) showed that none of the evaluated beans were immune and resistant to CBB in Turkey and Serbia, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…All differences were considered significant at P<0.05. The KLS data was transformed using square root transformation (Equation 3.3) in order to run a t test (St-Pierre et al, 2018, Bishara and Hittner, 2012, Mandizvo et al, 2016 Equation 3.3…”
Section: Discussionmentioning
confidence: 99%